APPLICATION OF ANIMATION VIDEO LEARNING MEDIA IN SCIENCE LEARNING ON THE WATER CYCLE MATERIAL FOR GRADE III AT SD N 24 LUBUKLINGGAU - Vieonalia senjarianty (CV Grasta Glory, 2025)
This study looks to find out how using animated videos for learning affects students' performance in Natural and Social Sciences (IPAS), focusing on the water cycle topic for Grade III at SD Negeri Biaro Lama. The background of this research lies in the low learning outcomes of students in IPAS, caused by the limited use of engaging and appropriate instructional media suited to elementary students' characteristics. This study uses a quantitative approach with a quasi-experimental method, employing a one-group pre-test and post-test design. The research subjects were all 20 students in Grade III. Data collection techniques involved multiple-choice tests consisting of 13 validated questions. The pre-test results showed that none of the students achieved the Minimum Mastery Criteria (KKM) of 70, with an average score of only 50.40. After the treatment using animated video learning media, post-test results showed a significant increase, with an average score of 85.40 and 18 students (90%) achieving mastery. Based on the hypothesis testing using a Z-test, the obtained Zcount was 6.60, greater than the Ztable of 1.64. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted, indicating that the use of animated video learning media significantly improves student learning outcomes. Animated video learning media has proven to be an effective tool in enhancing student engagement and understanding of scientific concepts in IPAS. This research suggests that future studies explore the application of animated media in other subject areas and across different grade levels to strengthen the generality of the findings. Keywords: learning media, animated video, learning outcomes, IPAS, water cycle.